Basis of optimal concentration of active pharmaceutical ingredients in combdrugs for external use with antimycotic activity - V. V. Luc; Y. L. Kolicheva; V. V. Gladishev; A. P. Lisyanska (The State Expert Center of the Ministry of Health of Ukraine, 2018)
An analysis of the state of modern resources for pharmacotherapy of foot mycosis was carried out. It showed that the creation of semisolid dosage forms for the topical skin, foot web space and nail treatment with bioactive compound from the group of nonspecific antimycotic substances (2-mercaptobenztiazol, chinozol) on the base of domestic technology ia actual for the modern pharmaceutical and medical science. Successful realization this project will allow to propose the effective complaentic and available for the wide segment of the Ukrainian medications for the effective foot mycisis therapy to the domestic dermatology and will make a real alternative imported pharmacotherapeutical preparations. The aim of this work is a scientifically basis of 2-mercaptobenztiazol and chinozol concentration in ointment's compositions for the foot mycosis therapy. Investigations of efficacy of model compositions on the sodium carboxymethylcellulose glycerogel base with combination of mebetizol and chinozol in concentration from 0 to 10% were carried out by the two-layer agar plate method against Candida albicans АТСС 885-653 according methematic model of two-factor experiment. It was ascertained that combining 2-mercaptobenztiazol and chinozol in semisolid dosage forms for external use allows to predict the potentiation of their action in mycosis topical therapy. At the same time both active pharmaceutical ingredients concentration makes a sighnificant influence on the antimycotic activity of experimental compositions. It was ascertained that chinozol concentration makes the greatest influence on the antimycotic activity of ointment compositions. At the same time 2-mercaptobenztiazol concentration and active pharmaceutical ingredients joint use in dosage form also make a statistically significant influence on the antimycotic activity level of semisolid dosage forms. Variance analysis of investigation's results showed that combining 10% 2-mercaptobenztiazol and 10% chinozol provides with optimal level of ointments specific activity. That fact allows to predict the advisability of making pastes on the base of these and active pharmaceutical ingredients combination in semisolid dosage forms for foot onychomycosis therapy. Results of antimycotic activity of ointments containing combinations of lower concentration of studied nonspecific antimycotic substances allow to propose them for the therapy of foot and interdigital space mycotic affections.